Managed retreat and coastal climate change adaptation: The environmental justice implications and value of a coproduction approach. (March 2022) - Tubridy, Fiadh; Lennon, Mick; Scott, Mark
Abstract: Due to the effects of climate change, coastal areas and communities around the world will be increasingly impacted by diverse hazards including sea-level rise, flooding and eroding shorelines, leading to increasing displacement of people. Managed retreat is one potential adaptation strategy to proactively plan for large-scale climate-related displacements. There is, however, evidence that in many cases managed retreat has had problematic social impacts and that it has frequently been implemented through top-down models of planning. In response, this article reviews the literature on managed retreat to identify the limitations of current practices and the challenges for a more environmentally just approach. Based on this review, the article argues that a coproduction approach would provide a means to help address key planning challenges in this field. This involves collecting local knowledge of the risks posed by climate hazards and/or retreat, creating a connection between local knowledge and institutional mechanisms for supported relocation and facilitating community-led processes of retreat and redevelopment. The key contribution of the article is its analysis of the value of a coproduction approach from the perspective of achieving a more environmentally just approach to managed retreat. Highlights: Managed retreat frequently has environmentally unjust implications. Coproduction is a potential means to ensure more environmentally just retreat. It would involve gathering local knowledge of the risks of climate change and retreat. It requires connections between local knowledge and institutional decision-making. It could involve wholly community-led processes of relocation and redevelopment.